Solid Lipid Nanoparticles Hydroquinone-Based for the Treatment of Melanoma: Efficacy and Safety Studies - Sonia Trombino; Rocco Malivindi; Giuseppe Barbarossa; Roberta Sole; Federica Curcio; Roberta Cassano (MDPI AG, 2023)
Classical melanoma therapy has several side effects that are responsible for a decrease in the final therapeutic efficacy. It is possible that the drug is degraded before reaching the target site and is metabolized by the body itself, resulting in repeated doses being administered throughout the day and a decrease in patient compliance. Drug delivery systems avoid degradation of the active ingredient, improve release kinetics, prevent the drug from being metabolized before reaching the site of action, and improve the safety and efficacy profiles of adjuvant cancer therapy. The solid lipid nanoparticles (SLNs) based on hydroquinone esterified with stearic acid realized in this work represent a chemotherapeutic drug delivery system that is useful in the treatment of melanoma. The starting materials were characterized by FT-IR and 1H-NMR, while the SLNs were characterized by dynamic light scattering. In efficacy studies, their ability to influence anchorage-dependent cell proliferation was tested on COLO-38 human melanoma cells. Furthermore, the expression levels of proteins belonging to apoptotic mechanisms were determined by analyzing the role of SLNs in modulating the expression of p53 and p21WAF1/Cip1. Safety tests were conducted to determine not only the pro-sensitizing potential but also the cytotoxicity of SLNs, and studies were conducted to assess the antioxidant and anti-inflammatory activity of these drug delivery.